Community Empowerment Through the Harapan Family Program - Indra Lesang; Kayum Lila (Peneliti.net, 2021)
Welfare in general is the dream of every human being who lives in the world. But not all humans feel well-being. There are still many people living in poverty. To support and reduce the poverty rate, the government issued a policy of the Family Hope Program. The Family Hope Program is a social protection program that provides cash assistance to Very Poor Households with certain conditions. Therefore, based on this, it is necessary to study the empowerment of the community through the family of hope program. The results of this study indicate that 1) the researcher found that the weak role of the Department of Social Affairs, Women's Empowerment, and Child Protection in Morotai Island Regency was still in the passive category. because in some roles, involvement or escorting the implementation of the family of hope program is still waiting for the Regent's order, meaning that the implementation of escort by the Service is not his responsibility. 2) In the implementation of the Family Hope Program in Pandanga Village, researchers found that the implementation of the Family Hope Program did not work as it should, a number of problems were found, namely (1) recipients did not know which component category to receive PKH in, (2) there were a number of differences in the nominal amount of PKH, ( 3) PKH recipients in 2019 no longer receive in 2020, (4) the number of PKH 2020 recipients fluctuates according to the scheme set by the government. 3) the researcher found weak coordination between the Office and the assistants, even the village head. So that the problems that occur in the village are not known at all by the Department. Even when it was confirmed to the Office about the problems in the field, they handed over the coordination to the assistants.